Circulating cell free DNA: a marker to predict the therapeutic response for biological DMARDs in rheumatoid arthritis. (10th December 2016) - Hashimoto, Teppei; Yoshida, Kohsuke; Hashimoto, Naonori; Nakai, Ayako; Kaneshiro, Kenta; Suzuki, Kohjin; Kawasaki, Yoshiko; Shibanuma, Nao; Hashiramoto, Akira
Abstract: Aim: To evaluate the correlation between circulating cell‐free DNA (ccfDNA) in plasma and clinical disease activities in patients with rheumatoid arthritis (RA). Method: The study group included 30 patients with RA who started biological disease‐modifying anti‐rheumatic drugs (DMARDs) therapy. The concentration of ccfDNA in plasma was measured by quantitative real‐time polymerase chain reaction at baseline to 24 weeks in every 4‐week period from 30 patients and 21 healthy individuals. We also evaluated the correlation between ccfDNA and the clinical activity or the therapeutic response for biological DMARDs, using the simplified disease activity index (SDAI), Disease Activity Score of 28 joints (erythrocyte sedimentation rate) and the European League Against Rheumatism (EULAR) response criteria. Synovial fluid samples of knee joints were collected from 13 patients with RA and 12 with osteoarthritis (OA) to measure ccfDNA. Result: The concentration of ccfDNA in RA patients at baseline was higher than healthy controls ( P = 0.016). After introducing biological DMARDs, ccfDNA was increased until 8 weeks from the baseline, and decreased after 12 weeks. The average of SDAI was improved in all patients enrolled. At 12 weeks after treatment, 15 patients were good responders to the EULAR response criteria, nine showed moderate response and six showed no response. ccfDNA in good responders was increased until 8 weeks, while those of moderate or no response were not ( P = 0.042). In joint fluid of RA patients, ccfDNA was remarkably increased as compared to those from OA ( P = 0.00011). Conclusion: After introducing biological DMARDs, increase of ccfDNA at 8 weeks was associated with improvement of disease activities. Compared with biomarkers reported, ccfDNA is able to predict the early therapeutic effects of biological DMARDs in RA patients.